Association of MTHFR C677T variant genotype with serum folate and Vit B12 in Iranian patients with colorectal cancer or adenomatous polyps - Mahla Ghorbani; Marjan Azghandi; Reza Khayami; Javad Baharara; Mohammad Amin Kerachian (BMC, 2021)
Abstract Background The incidence of colorectal cancer (CRC) has increased during recent years in Iran and other developing countries. Clinical studies suggest that essential folate dietary intake and moderate deficiency of methylenetetrahydrofolate reductase (MTHFR) may protect and reduce the risk of CRC. The present study aimed to investigate the clinical significance of C677T polymorphism within the MTHFR gene and its correlation with the serum folate and Vit B12 in the Iranian population suffering from CRC. Methods Blood samples were taken from 1017 Iranian individuals (517 cases and 500 controls) who were referred for colonoscopy. TaqMan probe assay was performed for C677T MTHFR polymorphism. Sera were fractionated from the blood samples of 43 patients and controls and folate and Vit B12 concentrations were measured by a monobind kit. The correlation of MTHFR polymorphisms and folate/vitamin-B12 with CRC risk was analyzed. Results In the current study, we found the frequency of three different genotypes of MTHFR polymorphism in the Iranian population i.e., CC, CT, and TT, to be 51.31, 26.73, 21.96 and 61, 32.2, 6.8 in case and control groups, respectively. The homozygote genotype of MTHFR rs1801133 polymorphism is associated with an increased risk of CRC by 3.68, 1.42, and 3.74-fold in codominant, dominant, and recessive models respectively (p value < 0.01). Our study revealed that there was no significant difference between the amount of folate and Vit B12 in the case and control groups (p value > 0.05). Conclusions This study revealed that there was no significant difference between the amount of folate and Vit B12 in the case and control groups. Furthermore, our results demonstrated a higher risk association for 677TT and 677TT + C677T genotypes of MTHFR compared with 677CC carriers among CRC patients.